Digitalization of Drone Monitoring Process on Indonesia Ministry of Transportation - Dany Eka Saputra (Social Economics and Ecology International Journal (SEEIJ), 2020)
Drone has been used for various commercial activity due to its flexibility and cost efficiency. However, to ensure that each drone operation still obey safety regulation, each drone activity must be monitored and heavily regulated. The administrative process to fly a drone was cost and time consuming. All process must be conducted manually in Jakarta. This activity was conducted as part of consultancy for Directorate of Flight Navigation, Ministry of Transportation. The aim of this activity was to digitize the administrative process of drone operation. The result was a digitalization plan, which consist softwares needed for each administrative process, and implementation plan, which recommend the time and order of implementation.